GREEN-SYNTHESIZED ZINC OXIDE NANOPARTICLES FROM VERJUICE (Vitis vinifera) EXHIBIT HEPATOPROTECTIVE AND ANTIOXIDANT EFFECTS AGAINST CARBON TETRACHLORIDE -INDUCED TOXICITY IN MALE RATS - Aziz, Pola Z; Ismail, Treefa F (Science Journal of University of Zakho, 2025)
Drug-induced liver injury, particularly that caused by carbon tetrachloride (CCl₄), poses significant clinical challenges due to oxidative stress and limited therapeutic options. This study investigated the hepatoprotective and antioxidant potential of green-synthesized zinc oxide nanoparticles (ZnO-NPs) using verjuice extract from unripe grapes in a CCl₄–induced rat model. The ZnO-NPs were characterized using UV-visible spectroscopy, X-ray diffraction, fourier transform infrared (FTIR) scanning electron microscopy, and energy-dispersive X-ray spectroscopy (EDX) analyses. Twenty male Wistar rats were assigned to four groups: control, CCl₄ toxicity (1 mL/kg twice weekly for 4 weeks), co-treatment (CCl₄ + ZnO-NPs 50 mg/kg daily for 4 weeks), and ZnO-NP post-treatment (CCl₄ for 4 weeks followed by ZnO-NPs 50 mg/kg daily for 4 weeks). ZnO-NPs significantly restored superoxide dismutase (SOD) activity and decreased malondialdehyde (MDA) levels to near control values, while normalizing alanine aminotransferase (ALT), aspartate aminotransferase (AST), and alkaline phosphatase (ALP) activities. Histopathological evaluation confirmed near-complete recovery of hepatic and renal architectures. These results demonstrate that verjuice-synthesized ZnO-NPs exert potent antioxidant and regenerative effects through the preservation of endogenous defenses and promotion of tissue repair, and the green synthesis approach offers an eco-friendly, biocompatible nanotherapeutic strategy with promising applications for drug-induced liver injury
Keywords: Carbon tetrachloride; Green synthesis; Hepatoprotection; Liver function; Oxidative stress biomarkers; Superoxide dismutase